Digitalization Online Exam Cards in the Era of Disruption 5.0 using the DevOps Method - Qurotul Aini; Muhamad Yusup; Nuke Puji Lestari Santoso; Ayi Rakhmat Ramdani; Untung Rahardja (Universitas Negeri Makassar, 2021)
In the current 5.0 era, almost all documents are digitally packaged, and the university needs to adapt to ever-evolving technology. For students, the test card is essential as proof of the contest to carry out the final exam. However, in practice, some University Student Exam Card sheets still adopt the traditional nature of queues. This will cause problems if the exam card can be lost or damaged. Digitalization can disruption the world of education, especially Exam Cards that are digital and systematically stored on the website page. SiS + is a Student iLearning Services that can make it easier for Raharja University students to access all their lecture needs by digitizing them. The YII Framework-based SiS + website's development uses the DevOps method to get online exam cards because applicable regulations fulfill student attendance. This research is expected to transform the student management system efficiency, reduce queues, and implement physical distancing during a pandemic.